Factors influencing endometrial receptivity in women with recurrent implantation failure - Katarzyna Opuchlik; Katarzyna Pankiewicz; Piotr Pierzyński; Janusz Sierdziński; Elina Aleksejeva; Andres Salumets; Tadeusz Issat; Piotr Laudański (BMC Women's Health)
Abstract Background Embryo implantation involves two key elements: a good quality embryo and receptive endometrium. Endometrial receptivity abnormalities are known as one of the possible causes of recurrent implantation failure (RIF), especially when the embryo is euploid. This study was aimed to evaluate the impact of age and other clinical factors on endometrial receptivity in women with RIF. Methods 68 women with RIF (defined as at least three unsuccessful transfers of good quality embryo of at least 1BB category of blastocysts) and 49 controls (women undergoing IVF treatment because of idiopathic infertility or male factor) were included to the study. After preparation of the endometrium by the hormone replacement therapy endometrial biopsies were taken from each patient and sequenced with beREADY test TAC targeting 67 biomarker genes for endometrial receptivity. Depending on the test result patients were classified into one of four different groups: pre-receptive (n = 16), early-receptive (n = 54), receptive (n = 44) and late-receptive (n = 3). Results In women with RIF pre-receptive endometrium has been detected substantially more often than in controls − 13 (19,1%) vs. 3 (6,1%) patients (p = 0,043). Early-receptive endometrium was diagnosed in the majority of patients with idiopathic infertility − 12 (66.7%) vs. 6 (33.3%) women (p = 0.042) and with polycystic ovary syndrome (PCOS) − 12 (70,6%) vs. 3 (17.7%) women (p = 0,0447). We found significant association between abnormal endometrial receptivity and patient’s age and duration of infertility. Young women were diagnosed significantly more often as normal or late-receptive, whereas older women with longer history of infertility as early-receptive and pre-receptive. Conclusions In patients with RIF in comparison to other women undergoing IVF procedures, patient’s age and infertility duration are the most important factors related to endometrial receptivity abnormalities, indicating that older women with a longer history of infertility may benefit the most from endometrial receptivity testing. Trial registration Not applicable.